Efektifitas Media Booklet Terhadap Pengetahuan Jenis Tumbuhan Paku Pada Mahasiswa Program Studi Pendidikan Biologi: (The Effectiveness of Booklet Media on Knowledge Types of Ferns in Students Biology Education Study Program) - Muswita Muswita; Upik Yelianti; Pinta Murni (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2021)
One of the obstacles faced by students in studying plant taxonomy is the difficulty of recognizing various types of ferns. The purpose of the study was to develop a media booklet on knowledge of fern species in Biology Education study program students. The research method is a quasi experimental design (Pretest-Posttest Control Group Design). The instrument is a written test sheet in the form of multiple choice. The pretest and posttest data were analyzed using SPSS using the paired sample t-test, then continued with the independent sample t-test. Test data independent sample t test obtained Sig. (2-tailed) of 0.000 < 0.05. N-Gain Score, shows the average value of N for the experimental class is 69.79 which is included in the